ULUL ALBAB DALAM AL-QUR’AN (TAFSIR TEMATIK) - ST Magfirah (Aqlam: Journal of Islam and Plurality, 2021)
Abstract: Ulul albab in the Qur´an discusses people who use their minds to think and make remembrance of natural phenomena and the power of Allah swt. There are sixteen times the derivation of ulul albab verses in the Qur'an, therefore this study uses thematic interpretation studies. This study formulates how to understand the characteristics of ulul albab in the Qur´an?. This research method uses thematic analysis with a philosophical and exgesic approach. This research is a literature review conducted by collecting data and analyzing data according to primary and secondary sources. The results of this study conclude that the concept of ulul albab in the Qur'an is someone who has broad insight and has sharpness in analyzing a problem, and ulul albab is referred to as someone who has the advantage of always getting closer to Allah by remembering (z\ikr) and think (tafakkur).Keywords: Ulul Albab, Thematic Exegesis, The Holy al-Qur´an, Z|ikr, Tafakku>r. Abstrak: Ulul albab dalam Al-Qur´an membahas tentang orang-orang yang menggunakan akal untuk berpikir dan berzikir terhadap fenomena alam dan kekuasaan Allah swt. Terdapat enam belas kali derivasi ayat-ayat ulul albab dalam Al-Qur´an oleh sebabnya penelitian ini menggunakan kajian tafsir tematik. Penelitian ini merumuskan bagaimana memahami karakteristik ulul albab dalam al-Qur´an?. Metode penelitian ini menggunakan analisis tematik dengan pendekatan filosofis dan eksegesis Penelitian ini bersifat kajian pustaka yang dilakukan dengan cara mengumpulkan data dan menelaah data sesuai dengan sumber primer dan sekunder. Hasil penelitian ini menyimpulkan bahwa konsep ulul albab dalam Al-Qur´an menggambarkan seseorang yang memiliki wawasan yang luas dan mempunyai ketajaman dalam menganalisis suatu permasalahan, serta selalu mendekatkan diri kepada Allah dengan cara mengingat (z\ikr) dan memikirkan (tafakkur). Kata Kunci: Ulul Albab, Tafsir Tematik, al-Qur´an, Zikir, Tafakkur.